Growth of mixed cultures of moderate thermophiles for commercial heap bioleaching of low-grade copper-sulphide ores - Ngulube, Qubekani (Department of Chemical Engineering, 2025)
Heap bioleaching has been demonstrated as an economic technology for processing low grade and recalcitrant copper-sulphide ores which would otherwise be uneconomic to process using conventional methods of mineral extraction such as concentration followed by smelting or autoclaving. Heap bioleaching has lower operating costs compared to other metallurgical methods. Naturally, a bioleach heap can be colonised by the indigenous micro organisms but the need to shorten process times and to increase efficiency has resulted in a need to inoculate the heaps. The aim of inoculation is to deliver micro-organisms best suited for the conditions expected in a heap as leaching progresses and as the heap ages. Successful leaching of primary copper-sulphide ores such as chalcopyrite has been shown to require thermophilic temperatures. Therefore, an inoculum with micro-organisms that facilitate the increase of temperature in the bioleach heap is required. Successful inoculation of a thermophilic bioleach heap requires a fundamental understanding of microbial growth on the ore at different temperature ranges. Furthermore, successful preparation and maintenance of suitable inocula also requires an understanding of culture conditions that could affect the micro-organisms in the stock cultures. This study focused on investigating the growth of bioleaching micro-organisms at 50°C, a moderate thermophilic temperature. This temperature is of particular interest as a ramping temperature from ambient to thermophilic temperatures. It is well known that efficient progression through the moderately thermophilic region can be a challenge. In the first part of the study, the aim was to characterise microbial growth in a bioleach heap environment. This was carried out in a controlled environment to allow for an independent study to determine growth rates of the component species in the community on low-grade ore as well as studying the effect of different microbial compositions of the inocula and the copper concentrations on the growth rates of a consortium of selected bioleaching micro-organisms. A simulated heap environment was created by packing a series of identical laboratory glass columns with low grade chalcopyrite ore and inoculating the columns with consortia of moderate thermophiles implicated in bioleaching. Physicochemical parameters such as Eh, pH, soluble copper and iron were monitored every second day in the pregnant liquid solution from the columns for a maximum of 50 days in each experiment. Assuming uniformity across all the columns in a series, columns were sacrificed at regular intervals to determine the microbial composition on the ore. Microbial assays included cell counts and quantification of microbial species using quantitative real-time polymerase chain reaction (qPCR) analysis with universal and species-specific primers. The microbial community from a single column was taken to be representative of all the columns in the series at a particular instance. Microbial community analyses using qPCR showed that all the four major microbial species detected in the inocula i.e. Acidithiobacillus caldus, Acidiplasma cupricumulans, Acidithiomicrobium species and Metallosphaera species colonised the ore, albeit at different rates. The growth rates of individual microbial species were observed to vary in response to the changing physicochemical and biological environment in the ore. The maximum specific growth rates in the whole ore bioleach heap environment were reported. Regardless of the starting composition of the inoculum, At. caldus, a sulphur-oxidiser was shown to be the first species to dominate the columns and was succeeded by Acidithiomicrobium spp. or Metallosphaera spp., the iron- and sulphur-oxidisers over time. Copper concentration was observed to affect microbial growth. Substantial growth and attachment of micro-organisms to the ore took place up to 5.0 g/L Cu in the irrigation solution but beyond this concentration the growth was minimal. At 10.0 and 15.0 g/L Cu, no detectable microbial growth occurred on the ore and the micro-organisms were only detected in the PLS, indicating that the micro-organisms could not attach strongly to the ore at higher Cu concentration. The second part of the study assayed microbial growth in a liquid culture environment used to prepare inocula for the heaps, paying particular attention to Acidithiomicrobium species, a key iron- and sulphur-oxidising moderate thermophile. The effect of carbon dioxide concentration and agitation speed on the microbial composition of a mixed moderate thermophilic culture was investigated. Three stirred tank reactors (STRs) and a shake flask were inoculated with the culture and maintained at 50 °C. Two STRs were sparged with air enriched to 1 % CO2 content while the third STR was sparged with normal air. One CO2 enriched STR was agitated at 550 rpm whilst the other two STRs were agitated at 250 rpm. The shake flask was not sparged and was agitated at 180 rpm. The cultures were monitored for 98 days and their microbial composition assayed weekly using cell counts and qPCR analysis. Eh, pH, iron and copper were also monitored. Similar physicochemical conditions occurred across all the reactors. Microbial community analysis using qPCR showed that the CO2 concentration in normal air did not limit the growth of Acidithiomicrobium spp. at an agitation speed of 250 rpm i.e. sparging with air enriched to 1 % CO2 was not beneficial at low agitation speed. A higher agitation speed of 550 rpm was detrimental to Acidithiomicrobium spp. Furthermore, the effect of Cu concentration on the microbial composition of the mixed culture was investigated. Growth of Acidithiomicrobium spp. was inhibited by an additional 2.5 g/L Cu in solution and the inhibition increased with increasing Cu concentration. On day 20 of the experiment, the presence of Acidithiomicrobium spp. in the reactors with the initial Cu concentration of 2.5, 5.0 and 7.5 g/L was reduced by 17 %, 50% and 88 %, respectively with respect to the Control. The amount of Acidithiomicrobium spp. present was observed to recover over the duration of the experiment, up to 5 g/L Cu suggesting the potential for acclimatisation to Cu. At higher Cu concentration, this species did not recover for the entire 127 days of the experiment. This work describes both microbial growth and colonisation of a bioleach heap, and inocula preparation. The work contributes a fundamental understanding of microbial growth on the ore and in liquid culture at species level. This is important for a successful design of suitable inocula and for optimisation of microbial succession during thermophilic heap bioleaching particularly to get to high temperatures through the moderate thermophile zone. The process management of a heap is particularly important at 50 to 55 °C owing to less biodiversity and activity of acidophiles in this temperature range. This work shows microbial succession at 50 °C. Sulphur-oxidisers dominate first as sulphur oxidation produces more energy for biomass growth than iron oxidation. Sulphur oxidation produces the heat required to raise the temperature to levels conducive for the growth of moderate thermophiles; subsequently the sulphur-oxidisers are succeeded by the combined iron- and sulphur-oxidisers over time. Finally, the importance of culture conditions was also shown. It was indicated that microbial species respond differently to copper and agitation speed, affecting the ecology of the inoculum, whilst the CO2 was shown to have no effect across the conditions studied. Through understanding microbial growth and colonisation of low-grade ore, and inocula preparation, minimisation of the time required to raise the temperature in thermophilic bioleach heap, and therefore allow value to be derived from the heap, can be achieved